2013
DOI: 10.1007/978-1-62703-411-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies and Intrabodies Against Huntingtin: Production and Screening of Monoclonals and Single-Chain Recombinant Forms

Abstract: Antibodies can be extremely useful tools for the field of triplet repeats diseases. These reagents are important for localizing proteins in tissues and they can be used in the isolation and characterization of the components of protein complexes. In the context of huntingtin (Htt), antibodies can distinguish Htt with normal or an expanded polyglutamine (polyQ) repeats, and they can identify distinct conformations of Htt. Htt is the protein that, when mutated to contain an expanded polyQ motif, causes Huntingto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Furthermore, MW8 has been utilized for immunoassays of human brain lysates to specifically detect aggregated Htt (Morozova et al, 2015; Reindl et al, 2019). The differences in IHC staining patterns may reflect the different conformations of Htt aggregates in the mouse and human brain respectively, with the MW8 epitope buried within aggregates in human tissue and inhibiting antibody binding (Khoshnan et al, 2013). Formic acid was utilized for antigen retrieval in this study to limit the effects of antigen masking, but the epitope of MW8 is very short (amino acids 83-90) and might have still been inaccessible within the structure of aggregated Htt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, MW8 has been utilized for immunoassays of human brain lysates to specifically detect aggregated Htt (Morozova et al, 2015; Reindl et al, 2019). The differences in IHC staining patterns may reflect the different conformations of Htt aggregates in the mouse and human brain respectively, with the MW8 epitope buried within aggregates in human tissue and inhibiting antibody binding (Khoshnan et al, 2013). Formic acid was utilized for antigen retrieval in this study to limit the effects of antigen masking, but the epitope of MW8 is very short (amino acids 83-90) and might have still been inaccessible within the structure of aggregated Htt.…”
Section: Discussionmentioning
confidence: 99%
“…This result can be justified for the antibody D7F7, which has previously been shown to react with human Htt expressed in mouse models of HD but not in human tissue, due to the differential processing of human Htt in the mouse versus the human brain (Franich et al, 2018). Previous studies suggest that antigen masking could have prevented the remaining antibodies from binding Htt at their respective epitopes, with that region of the protein buried inside an aggregate (Khoshnan et al, 2013). However, formic acid treatment was carried out for antigen unmasking to overcome this limitation, and most of these antibodies’ epitopes are downstream of the Htt N-terminus and thought to be excluded from aggregates (Schilling et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Misfolded and aggregated N-terminal fragments of mutant huntingtin (mhtt) accumulate in the neuronal nuclei and processes and lead to neurodegeneration, although the exact pathways involved in this process remain unclear [reviewed in 114 ]. Intrabody-mediated modulation of toxic htt aggregates represent an alternative therapeutic approach for HD [ 24 , 35 , 115 ]. Thus, it has been shown that the anti-N-terminal htt (residues 1-17) C4 scFv intrabody inhibits aggregate formation in cell cultures and prevents toxicity in an organotypic slice culture model of HD [ 116 - 118 ].…”
Section: Introductionmentioning
confidence: 99%